Experimental study on energy dissipation and fragmentation characteristics of gas-bearing coal under combined dynamic and static loading - Huaiqian LIU; Hongbao ZHAO; Lei WANG; Qing MA; Meilu YU; Hao HU; Chunhua WANG (Meitan xuebao)
To explore the energy dissipation and fragmentation characteristics of gas-bearing coal under combined dynamic and static load, the impact experiment of gas-bearing coal under different impact velocities and axial compressive stress ratios was carried out with the help of the self-developed observable combined dynamic and static loading test system of gas-bearing coal. The energy evolution laws and energy dissipation characteristics of gas-bearing coal fracture were studied. The debris ejection mechanism and its distribution characteristics were discussed, the intrinsic relationship between the energy dissipation density and the debris fractal dimension of gas-bearing coal was clarified. The results show that: ① The energy conversion of gas-bearing coal during impact is synchronous, and the time curve of dissipation energy corresponds to the deformation stage of coal sample, that is, it is found that when the bearing capacity of gas-bearing coal is lost after impacted, the dynamic stress-strain curve is parabolic, and the time curve of dissipation energy can be divided into elastic-energy storage stage, elastic-plastic-energy dissipation stage, plastic-energy dissipation stage and energy release stage. Especially, when the axial load causes the gas-bearing coal to be in an elastic-plastic or plastic state, the time curve of dissipation energy is divided into the elastic-plastic or plastic energy dissipation stage and the energy release stage. When the gas-bearing coal still has bearing capacity after impacted, the dynamic stress-strain curve is barbed, and the deformation stage can be divided into elastic stage, elastic-plastic stage, plastic stage and rebound stage. the time curve of dissipation energy is correspondingly divided into elastic-energy storage stage, elastic-plastic-energy dissipation stage, plastic-energy dissipation stage and energy-rebound stage. The energy rebound stage can lead to coal wall spalling or roadway rockbursts. ② The dissipation energy of gas-bearing coal increases with the impact velocity increasing, the dissipation energy ratio is basically constant, which is between 31.1%−34.0%. The fractal dimension of debris increases exponentially with the increase of energy dissipation density. There is a critical axial compressive stress ratio, which makes the dissipation energy and its ratio decrease first and then increase. The fractal dimension of debris is segmented with the change of energy dissipation density: when the sample is in the continuous energy-storage stage, the fractal dimension of debris decreases with the increase of energy dissipation density，when the sample is in the continuous energy-release stage, the fractal dimension of debris increases with the energy dissipation density increasing, and at this point, slight disturbances can lead to coal-rock instability. These conclusions enrich the basic theory of the dynamic coal–rock–gas disaster induction mechanism and can provide theoretical support for the monitoring, early warning and prevention technology of dynamic disasters in composites.